Advance care directive prevalence among older Australians and associations with person‐level predictors and quality indicators. (1st May 2021) - Buck, Kimberly; Nolte, Linda; Sellars, Marcus; Sinclair, Craig; White, Ben P.; Kelly, Helana; Macleod, Ashley; Detering, Karen M.
Abstract: Background: Advance care planning (ACP) conversations may result in preferences for medical care being documented. Objective: To explore the uptake and quality of advance care directives (ACDs) among older Australians accessing health and aged care services, by overall ACP documentation prevalence, person‐level predictors and ACD quality indicators. Design and Setting: National multi‐centre health record audit in general practices (GP), hospitals and residential aged care facilities (RACF). Participants: A total of 4187 people aged ≥65 years attending their GP (n = 676), admitted to hospital (n = 1122) or residing in a RACF (n = 2389). Main Outcome Measures: ACP documentation prevalence by setting and type including person‐completed ACDs and non‐ACD documents (completed by a health professional or someone else); person‐level predictors and quality indicators of ACDs. Results: Overall ACP documentation prevalence was 46.5% (29.2% weighted). ACD prevalence was 25.3% (14.2% weighted). Unweighted ACD prevalence was higher in RACFs (37.7%) than in hospitals (11.1%) and GPs (5.5%). 35.8% of ACP documentation was completed by a health professional (9.7% weighted), and 18.1% was completed by someone else (10.6% weighted). Having an ACD was positively associated with being female, older, having two or more medical conditions, receiving palliative care, being divorced/separated and being in a RACF. Only 73% of ACDs included full name, signature, document date and witnessing. Conclusions and Contribution: Low ACP documentation prevalence and a lack of accessible, person‐completed and quality ACDs represent an important ACP implementation issue. Low prevalence is complicated by poor document quality and a higher prevalence of documents being completed by someone other than the person.